Epoxy resin, curable resin composition, cured product and carbon fiber-reinforced composite material

JP2025025222APending Publication Date: 2025-02-21NIPPON KAYAKU CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023129808
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2025-02-21

Smart Images

  • Figure 2025025222000007
    Figure 2025025222000007
  • Figure 2025025222000008
    Figure 2025025222000008
  • Figure 2025025222000001
    Figure 2025025222000001
Patent Text Reader

Abstract

To provide: an epoxy resin having excellent heat resistance; a curable resin composition containing the epoxy resin; and a carbon fiber-reinforced composite material formed by curing these materials.SOLUTION: An epoxy resin is obtained by making a phenolic compound represented by formula (1) react with an epihalohydrin. (In formula (1), dotted lines between C1 and C2, between C2 and C3, between C3 and C4, between C4 and C5, between C5 and C6, and between C6 and C1 respectively indicate that a single bond or a double bond may exist as long as the valence is allowable, m and n are each an average value of the number of repetitions, m and n are real numbers satisfying 1<m≤5 and 1<n≤10 respectively.)SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an epoxy resin having a specific structure, a curable resin composition, a cured product, and a carbon fiber reinforced composite material. [Background technology]

[0002] By curing epoxy resins with various curing agents, they become cured products with excellent mechanical properties, water resistance, chemical resistance, heat resistance, and electrical properties, and are used in a wide range of fields such as adhesives, paints, laminates, molding materials, and casting materials. Carbon fiber reinforced composite materials (CFRP), which are made by impregnating and curing reinforcement fibers with epoxy resin and a curing agent as a matrix resin, can be given properties such as light weight and high strength, and in recent years they have been widely used in aircraft structural members, wind turbine blades, automobile exterior panels, and computer applications such as IC trays and laptop computer housings, and demand for them is increasing. In particular, they are used as matrix resins for aircraft applications, taking advantage of the light weight and high strength properties of the molded products.

[0003] In particular, fiber-reinforced plastic molded products made with reinforcing fibers have attracted attention for their lightweight yet excellent mechanical strength characteristics, and their use is expanding in a variety of structural applications, including housings and various components for automobiles, aircraft, ships, etc. In particular, as the application of carbon fiber reinforced composite materials (CFRP) to the aircraft and automobile fields expands, the amount of epoxy resin used as its matrix resin is steadily increasing.

[0004] Traditionally, many of the raw materials used for epoxy resins and hardeners have been derived from petroleum. However, in recent years, concerns have arisen about the depletion of petroleum resources, and methods of recycling many materials, such as using renewable resources such as plants or decomposing the hardened materials, are being investigated. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 04-117420 Summary of the Invention [Problem to be solved by the invention]

[0006] Patent Document 1 describes an epoxy resin that uses raw materials derived from biomass. However, the epoxy resin described in Patent Document 1 has low heat resistance and poor mechanical properties such as bending strength and bending modulus, so there are issues with its application as a CFRP material.

[0007] The present invention has been made in consideration of the above-mentioned circumstances, and an object of the present invention is to provide an epoxy resin having excellent heat resistance, a curable resin composition containing the epoxy resin, and a carbon fiber reinforced composite material obtained by curing the epoxy resin or the cured composition. [Means for solving the problem]

[0008] That is, the present invention is as shown in the following [1] to [7]. In the present invention, "(Numerical value 1) to (Numerical value 2)" indicates that the upper and lower limits are included. [1] An epoxy resin obtained by reacting a phenol compound represented by the following formula (1) with epihalohydrin.

[0009] [ka]

[0010] (In formula (1), C 1 and C. 2 Between 2 and C. 3 Between 3 and C. 4 Between 4 and C. 5 Between 5 and C. 6 Between and C 6 and C. 1The dotted line between them indicates that a single bond or a double bond may exist within the range allowed by the valence. m and n are the average values of the repetition numbers respectively, and m is a real number satisfying 1 < m ≦ 5, and n is a real number satisfying 1 < n ≦ 10.) [2] The epoxy resin according to the preceding item [1], wherein the phenolic compound represented by the formula (1) is obtained by adding phenols to a cyclic terpene compound. [3] The epoxy resin according to the preceding item [1], having an epoxy equivalent of 280 g / eq. or more and 600 g / eq. or less. [4] A curable resin composition containing the epoxy resin according to any one of the preceding items [1] to [3] and a curing agent. [5] A cured product obtained by curing the curable resin composition according to the preceding item [4].[[]END]] [6] A carbon fiber reinforced composite material obtained by curing the curable resin composition according to the preceding item [4].[[]END]] [7] The epoxy resin according to the preceding item [1], wherein the phenolic compound represented by the formula (1) is YS Polyster K125 (trade name, manufactured by Yasuhara Chemical Co., Ltd.) [Effect of the Invention]

[0011] According to the present invention, it is possible to provide an epoxy resin, a curable resin composition, and a carbon fiber reinforced composite material obtained by curing these, the cured products of which are excellent in heat resistance. [Brief Description of the Drawings]

[0012] [Figure 1] It is a GPC chart of the epoxy resin of Example 1. [Diagram 2] It is a GPC chart of the epoxy resin of Comparative Example 1.

[0013] Hereinafter, embodiments according to the present invention (hereinafter also referred to as "the present embodiment") will be described in more detail.

[0014] The epoxy resin of this embodiment is obtained by reacting a phenol resin represented by the following formula (1) with epihalohydrin.

[0015]

Chemical formula

[0016] (In formula (1), between C 1 and C 2 , between C 2 and C 3 , between C 3 and C 4 , between C 4 and C 5 , between C 5 and C 6 , and between C 6 and C 1 The dotted lines indicate that a single bond or a double bond may exist within the range allowed by the valence. m and n are respectively the average values of the repetition numbers, and m is a real number satisfying 1 < m ≤ 5, and n is a real number satisfying 1 < n ≤ 10.)

[0017] In the above formula (1), the values of m and n can be calculated from the number average molecular weight determined by gel permeation chromatography (GPC, detector: RI), gas chromatography (GC-MS, ionization method: EI), NMR measurement, or the area ratio of each separated peak. m is a real number satisfying 1 < m ≤ 5, preferably a real number satisfying 3 ≤ m ≤ 5. n is a real number satisfying 1 < n ≤ 10, preferably a real number satisfying 1 < n ≤ 5, and more preferably a real number satisfying 3 ≤ n ≤ 5.

[0018] The phenolic resin represented by the formula (1) is obtained by subjecting a cyclic terpene compound to an addition reaction with a phenol. The raw material cyclic terpene compound may be a monocyclic terpene compound or a bicyclic terpene compound, and specific examples thereof include α-pinene, β-pinene, α-terpinene, β-terpinene, γ-terpinene, 3,8-menthadiene, 2,4-menthadiene, limonene, and terpinolene. In addition, the other raw material phenol for producing a cyclic terpene skeleton-containing polyhydric phenol compound includes catechols, resorcinols, and hydroquinones as disubstituted phenols, and phenol, bisphenol A, and bisphenol F as monosubstituted phenols, and may be used alone or in combination of two or more kinds. In addition, an example of a commercially available product of the phenolic compound represented by the formula (1) is YS Polystar K125 (trade name, manufactured by Yasuhara Chemical Co., Ltd.), which has the following formula (2) as a representative structure.

[0019] [ka]

[0020] The epihalohydrin is easily available on the market. The amount of epihalohydrin used is usually 2.0 to 10 mol, preferably 3.0 to 8.0 mol, more preferably 3.5 to 6.0 mol, per mol of hydroxyl group of the phenolic resin represented by the formula (1). Preferred examples of epihalohydrin that can be used in this embodiment include epichlorohydrin, α-methylepichlorohydrin, β-methylepichlorohydrin, epibromohydrin, and the like, and epichlorohydrin, which is easily available industrially, is particularly preferred.

[0021] In the reaction between the phenolic resin represented by the formula (1) and epihalohydrin, an alkali metal hydroxide can be used as a catalyst for promoting the epoxidation step. Examples of alkali metal hydroxides that can be used include sodium hydroxide and potassium hydroxide. A solid or an aqueous solution thereof can be used, but in this embodiment, it is particularly preferable to use a solid formed into a flake shape from the standpoint of solubility and handling. The amount of the alkali metal hydroxide used is usually 0.90 to 1.5 mol, preferably 0.95 to 1.25 mol, and more preferably 0.99 to 1.15 mol, per mol of hydroxyl groups in the raw material phenol mixture.

[0022] In order to promote the reaction, a quaternary ammonium salt such as tetramethylammonium chloride, tetramethylammonium bromide, trimethylbenzylammonium chloride, etc. may be added as a catalyst. The amount of the quaternary ammonium salt used is usually 0.1 to 15 g, preferably 0.2 to 10 g, per mole of hydroxyl groups in the raw material phenol mixture.

[0023] The reaction temperature is usually 30 to 90° C., preferably 35 to 80° C. In particular, in this embodiment, for higher purity epoxidation, a temperature of 50° C. or higher is preferred, and particularly 60° C. or higher is preferred. The reaction time is usually 0.5 to 10 hours, preferably 1 to 8 hours, and particularly preferably 1 to 3 hours. If the reaction time is too short, the reaction will not proceed to completion, and if the reaction time is too long, by-products will be produced, which is undesirable.

[0024] The reaction product of these epoxidation reactions is washed with water or heated under reduced pressure to remove epihalohydrin and solvent. Furthermore, in order to obtain an epoxy resin with a smaller amount of hydrolyzable halogen, the recovered epoxy resin can be dissolved in a ketone compound having 4 to 7 carbon atoms (e.g., methyl isobutyl ketone, methyl ethyl ketone, cyclopentanone, cyclohexanone, etc.) as a solvent, and an aqueous solution of an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide is added to carry out the reaction to ensure ring closure. In this case, the amount of the alkali metal hydroxide used is usually 0.01 to 0.3 mol, preferably 0.05 to 0.2 mol, per mol of hydroxyl group in the raw material phenol mixture used in the epoxidation. The reaction temperature is usually 50 to 120°C, and the reaction time is usually 0.5 to 2 hours.

[0025] After the reaction is completed, the salt formed is removed by filtration, washing with water, or the like, and the solvent is then distilled off under heating and reduced pressure to obtain the epoxy resin of the present embodiment.

[0026] The epoxy resin of this embodiment preferably has a weight-average molecular weight of 500 or more and 4500 or less, more preferably 600 or more and 3000 or less, and even more preferably 800 or more and 2000 or less. When the weight-average molecular weight is less than 500, it is difficult to obtain the effect of improving heat resistance due to an increase in molecular weight. On the other hand, when the weight-average molecular weight is more than 4500, in addition to making it difficult to purify the resin by washing with water or the like, the viscosity becomes too high when the resin is used in a carbon fiber reinforced composite material, and the fluidity cannot be ensured, impregnation and wettability of the fibers is impaired, and the fluidity of the prepreg is difficult to ensure.

[0027] The epoxy resin of this embodiment preferably has an epoxy equivalent of 280 g / eq. or more and 600 g / eq. or less, and more preferably 300 g / eq. or more and 500 g / eq. or less. If the epoxy equivalent is less than 280 g / eq., the water absorption rate of the cured product becomes high, making it difficult to use it in carbon fiber reinforced composite materials. If the epoxy equivalent is more than 600 g / eq., the viscosity becomes too high and fluidity cannot be ensured, impregnation and wettability of the fibers is impaired, making it difficult to ensure the fluidity of the prepreg.

[0028] The epoxy resin of the present embodiment preferably has a resinous form having a softening point, and the softening point is preferably from 40° C. to 120° C., and more preferably from 80° C. to 100° C. A softening point of 40° C. or higher means that the molecular weight distribution is appropriate or that there is no residual solvent, etc., and the heat resistance is good, and problems such as poor curing and voids during molding can be suppressed, while a softening point of 120° C. or lower provides good handling when kneaded with other resins.

[0029] The melt viscosity (150°C) of the epoxy resin of this embodiment is preferably 0.1 to 1.5 Pa·s. If the viscosity is higher than 1.5 Pa·s, problems will arise with fluidity, causing problems with flow and embeddability during pressing. If the viscosity is less than 0.1 Pa·s, the molecular weight will be too small and heat resistance will be insufficient. In the prepreg molding method for carbon fiber reinforced composite materials, low tackiness is desired, so the melt viscosity (150°C) is preferably 0.5 to 1.2 Pa·s.

[0030] The curable resin composition of the present embodiment contains the epoxy resin of the present embodiment and a curing agent. The heat resistance (Tg) of the curable resin composition of the present embodiment is preferably 160 to 300°C, more preferably 180 to 250°C. If the heat resistance is less than 160°C, it is difficult to apply it to components that require heat resistance, such as those around an aircraft engine, and the resin softens during use, significantly reducing mechanical strength, which is undesirable as it can lead to damage to the material. In addition, the heat resistance of an epoxy resin is generally correlated with the crosslink density, and the higher the crosslink density, the higher the heat resistance. In other words, if the heat resistance exceeds 300°C, the crosslink density increases, which is undesirable as the mechanical strength of the cured product becomes brittle.

[0031] Examples of the curing agent that can be used in the curable resin composition of the present embodiment include amine-based curing agents, acid anhydride-based curing agents, amide-based curing agents, and phenol-based curing agents.

[0032] In the curable resin composition of the present embodiment, an amine curing agent is preferred, since it can achieve a good balance between the resin viscosity of the curable resin composition and the heat resistance of the cured resin. Amine-based hardeners include 3,3'-diaminodiphenyl sulfone (3,3'-DDS), 4,4'-diaminodiphenyl sulfone (4,4'-DDS), diaminodiphenylmethane (DDM), 3,3'-diisopropyl-4,4'-diaminodiphenylmethane, 3,3'-di-t-butyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-diisopropyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-di-t-butyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetraethyl-4,4'-diaminodiphenylmethane, 3,3'-diisopropyl-5,5'-diethyl-4,4' -diaminodiphenylmethane, 3,3'-di-t-butyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetraisopropyl-4,4'-diaminodiphenylmethane, 3,3'-di-t-butyl-5,5'-diisopropyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetra-t-butyl-4,4'-diaminodiphenylmethane, diaminodiphenyl ether (DADPE), bisaniline, benzyldimethylaniline, 2-(dimethylaminomethyl)phenol (DMP-10), 2,4,6-tris(dimethylaminomethyl)phenol (DMP-30), 2-ethylhexanoic acid ester of 2,4,6-tris(dimethylaminomethyl)phenol, and the like can be used. Further examples include aniline novolak, orthoethylaniline novolak, aniline resins obtained by reacting aniline with xylylene chloride, and aniline resins obtained by polycondensation of aniline with substituted biphenyls (4,4'-bis(chloromethyl)-1,1'-biphenyl, 4,4'-bis(methoxymethyl)-1,1'-biphenyl, etc.) or substituted phenyls (1,4-bis(chloromethyl)benzene, 1,4-bis(methoxymethyl)benzene, 1,4-bis(hydroxymethyl)benzene, etc.).

[0033] Examples of the acid anhydride curing agent include phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, maleic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylnadic anhydride, hexahydrophthalic anhydride, and methylhexahydrophthalic anhydride.

[0034] Examples of the amide-based curing agent include dicyandiamide, or a polyamide resin synthesized from a dimer of linoleic acid and ethylenediamine.

[0035] Phenol-based hardeners include polyhydric phenols (bisphenol A, bisphenol F, bisphenol S, fluorene bisphenol, terpene diphenol, 4,4'-dihydroxybiphenyl, 2,2'-dihydroxybiphenyl, 3,3',5,5'-tetramethyl-(1,1'-biphenyl)-4,4'-diol, hydroquinone, resorcin, naphthalene diol, tris-(4-hydroxyphenyl)methane, and 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane, etc.); phenols (e.g., phenol, alkyl-substituted phenol, naphthol, alkyl-substituted naphthol, dihydroxybenzene, and dihydroxynaphthalene, etc.); and aldehydes (formaldehyde, acetaldehyde, benzaldehyde, p-hydroxybenzaldehyde, o-hydroxyphenyl, phenylmethylsulfonyl ... phenolic resins obtained by condensation of the above-mentioned phenols with substituted biphenyls (4,4'-bis(chloromethyl)-1,1'-biphenyl and 4,4'-bis(methoxymethyl)-1,1'-biphenyl, etc.) or substituted phenyls (1,4-bis(chloromethyl)benzene, 1,4-bis(methoxymethyl)benzene, 1,4-bis(hydroxymethyl)benzene, etc.); modified products of the above-mentioned phenols and / or the above-mentioned phenolic resins; and halogenated phenols such as tetrabromobisphenol A and brominated phenolic resins.

[0036] In the curable resin composition of the present embodiment, the amount of the curing agent used is preferably 0.7 to 1.2 equivalents relative to 1 equivalent of the epoxy group of the epoxy resin. When the amount is less than 0.7 equivalents relative to 1 equivalent of the epoxy group or exceeds 1.2 equivalents, curing may be incomplete and good cured physical properties may not be obtained.

[0037] In addition, in the curable resin composition of the present embodiment, a curing accelerator may be blended as necessary. The gelation time can also be adjusted by using a curing accelerator. Examples of the curing accelerator that can be used include imidazoles such as 2-methylimidazole, 2-ethylimidazole, and 2-ethyl-4-methylimidazole, tertiary amines such as 2-(dimethylaminomethyl)phenol and 1,8-diaza-bicyclo[5,4,0]undecene-7, phosphines such as triphenylphosphine, and metal compounds such as tin octylate. The curing accelerator is used in an amount of 0.01 to 5.0 parts by weight per 100 parts by weight of the epoxy resin as necessary.

[0038] In the curable resin composition of the present embodiment, other epoxy resins may be blended. Specific examples thereof include phenols (phenol, alkyl-substituted phenol, aromatic substituted phenol, naphthol, alkyl-substituted naphthol, dihydroxybenzene, alkyl-substituted dihydroxybenzene, dihydroxynaphthalene, etc.) and various aldehydes (formaldehyde, acetaldehyde, alkyl aldehyde, benzaldehyde, alkyl-substituted benzaldehyde, hydroxybenzaldehyde, naphthaldehyde, etc.). , glutaraldehyde, phthalaldehyde, crotonaldehyde, cinnamaldehyde, etc.), polymers of phenols and various diene compounds (dicyclopentadiene, terpenes, vinylcyclohexene, norbornadiene, vinylnorbornene, tetrahydroindene, divinylbenzene, divinylbiphenyl, diisopropenylbiphenyl, butadiene, isoprene, etc.), polymers of phenols and ketones (acetone, methyl ethyl ketone, methyl isobutyl ketone, acetophenone, benzo phenolic resins obtained by polycondensation of phenols and substituted biphenyls (4,4'-bis(chloromethyl)-1,1'-biphenyl and 4,4'-bis(methoxymethyl)-1,1'-biphenyl, etc.) or substituted phenyls (1,4-bis(chloromethyl)benzene, 1,4-bis(methoxymethyl)benzene, 1,4-bis(hydroxymethyl)benzene, etc.), polycondensates of bisphenols and various aldehydes, glycidyl ether epoxy resins obtained by glycidylating alcohols, alicyclic epoxy resins such as 4-vinyl-1-cyclohexene diepoxide and 3,4-epoxycyclohexylmethyl-3,4'-epoxycyclohexanecarboxylate, glycidyl amine epoxy resins such as tetraglycidyldiaminodiphenylmethane (TGDDM) and triglycidyl-p-aminophenol, and glycidyl ester epoxy resins, but are not limited to these, so long as they are commonly used epoxy resins.

[0039] The curable resin composition of the present embodiment may contain a known maleimide compound as necessary. Specific examples of the maleimide compound that can be used include 4,4'-diphenylmethane bismaleimide, polyphenylmethane maleimide, m-phenylene bismaleimide, 2,2'-bis[4-(4-maleimidophenoxy)phenyl]propane, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4-methyl-1,3-phenylene bismaleimide, 4,4'-diphenylether bismaleimide, 4,4'-diphenylsulfone bismaleimide, 1,3-bis(3-maleimidophenoxy)benzene, 1,3-bis(4-maleimidophenoxy)benzene, biphenylaralkyl type maleimide, etc., but are not limited thereto. These may be used alone or in combination of two or more. When the maleimide compound is blended, a curing accelerator is blended if necessary. The above-mentioned curing accelerators, as well as radical polymerization initiators such as organic peroxides and azo compounds can be used.

[0040] The curable resin composition of the present embodiment can also adjust the gelation time by using a curing accelerator. Examples of curing accelerators that can be used include imidazoles such as 2-methylimidazole, 2-ethylimidazole, and 2-ethyl-4-methylimidazole, tertiary amines such as 2-(dimethylaminomethyl)phenol and 1,8-diaza-bicyclo[5,4,0]undecene-7, phosphines such as triphenylphosphine, and metal compounds such as tin octylate. The curing accelerator is used in an amount of 0.01 to 5.0 parts by weight per 100 parts by weight of the epoxy resin, as necessary.

[0041] The curable resin composition of the present embodiment may further contain various additives as exemplified below, as necessary. However, the curable resin composition of the present embodiment is not limited to the additives below, and may contain various additives well known in the art, as necessary.

[0042] The curable resin composition of the present embodiment may further contain a flame retardant as necessary for the purpose of imparting flame retardancy. The flame retardant is not particularly limited, and examples thereof include phosphorus compounds such as red phosphorus coated with a thermal epoxy resin such as a phenolic resin, phosphoric acid esters, and triphenylphosphine oxide; nitrogen-containing compounds such as melamine, melamine derivatives, melamine-modified phenolic resins, compounds having a triazine ring, cyanuric acid derivatives, and isocyanuric acid derivatives; phosphorus and nitrogen-containing compounds such as cyclophosphazene; metal complex compounds such as dicyclopentadienyl iron; zinc compounds such as zinc oxide, zinc stannate, zinc borate, and zinc molybdate; metal oxides such as iron oxide and molybdenum oxide; metal hydroxides such as aluminum hydroxide and magnesium hydroxide; and composite metal hydroxides represented by the following composition formula (A). Examples of the flame retardant include known organic or inorganic compounds and metal hydroxides containing halogen atoms, antimony atoms, nitrogen atoms, or phosphorus atoms.

[0043] The curable resin composition of the present embodiment may further contain an inorganic filler as necessary. Specific examples of the inorganic filler include fine powders of fused silica, crystalline silica, glass, alumina, calcium carbonate, zirconium silicate, calcium silicate, silicon nitride, aluminum nitride, boron nitride, beryllia, zirconia, zircon, fosterite, steatite, spinel, mullite, titania, talc, clay, mica, etc., or beads obtained by sphering these.

[0044] Inorganic fillers having a flame retardant effect may be used, such as aluminum hydroxide, magnesium hydroxide, composite metal hydroxides such as a composite hydroxide of magnesium and zinc, and zinc borate.

[0045] When the curable resin composition contains an inorganic filler, its content is not particularly limited as long as the effect of this embodiment can be obtained. The content of the inorganic filler is preferably 50% by weight or more in the total weight of the curable resin composition, more preferably 60% by weight to 95% by weight from the viewpoint of flame retardancy, and even more preferably 70% by weight to 90% by weight. By containing an inorganic filler, the thermal expansion coefficient, thermal conductivity, elastic modulus, etc. of the cured product can be improved to desired properties. When the content of the inorganic filler is 50% by weight or more, the effect of improving these properties can be obtained more effectively. Also, when it is 95% by weight or less, the viscosity increase of the curable resin composition is more suppressed, sufficient fluidity is easily obtained, and moldability is further improved.

[0046] The curable resin composition of the present embodiment may further contain an antioxidant as necessary. This can prevent oxidation of the cured product of the curable resin composition, and can suppress weight loss of the cured product even when left in a high-temperature environment. Electrical properties are further improved.

[0047] Examples of the antioxidant include phenol-based antioxidants, phosphite-based antioxidants, sulfur-based antioxidants, hindered amine-based antioxidants, etc. These antioxidants may be used alone or in combination of two or more.

[0048] When the curable resin composition contains an antioxidant, the content is not particularly limited as long as the weight loss suppression effect is achieved. From the viewpoint of the heat resistance (high Tg) of the curable resin composition, the content of the antioxidant is preferably 0.5 parts by weight to 20 parts by weight, more preferably 1 part by weight to 10 parts by weight, based on 100 parts by weight of the total amount of the epoxy resin. By making the content of the antioxidant 0.5 parts by weight or more, the effect of suppressing the weight loss of the cured product can be sufficiently obtained, and by making the content of the antioxidant 20 parts by weight or less, the heat resistance (high Tg) of the cured product is suppressed from decreasing.

[0049] The curable resin composition of the present embodiment may further contain a coupling agent as necessary. This improves the adhesion between the resin component and the inorganic filler, and improves the electrical properties. The coupling agent may be appropriately selected from compounds that are commonly used. Examples of the coupling agent include known coupling agents such as various silane-based compounds such as epoxysilane, mercaptosilane, aminosilane, alkylsilane, ureidosilane, vinylsilane, styrylsilane, methacrylsilane, acrylicsilane, and sulfidosilane, titanium-based compounds, aluminum chelate compounds, and aluminum / zirconium-based compounds. Among these, silane-based compounds are preferred. These coupling agents may be used alone or in combination of two or more.

[0050] When the curable resin composition contains a coupling agent, the content is preferably 0.05 to 5.0 parts by weight, and more preferably 0.1 to 4.5 parts by weight, based on 100 parts by weight of the total amount of the inorganic filler. By making the content 0.05 parts by weight or more, the adhesion to the frame, etc. can be further improved.

[0051] The method for preparing the curable resin composition of the present embodiment is not particularly limited, but each component may be mixed uniformly or may be prepolymerized. For example, a mixture containing the compound of the present embodiment is heated in the presence or absence of a curing accelerator or a polymerization initiator, and in the presence or absence of a solvent to form a prepolymer. Similarly, an amine compound, a compound having an ethylenically unsaturated bond, a maleimide compound, a cyanate ester compound, polybutadiene and its modified products, polystyrene and its modified products, inorganic fillers, and other additives may be added to form a prepolymer. The mixing or prepolymerization of each component is carried out using, for example, an extruder, a kneader, a roll, or the like in the absence of a solvent, and a reaction kettle with a stirrer in the presence of a solvent.

[0052] The curable resin composition of this embodiment is obtained by uniformly mixing the above components. The curable resin composition of this embodiment can be easily made into a cured product by a method similar to that of a conventionally known method. For example, the curable resin composition of this embodiment is obtained by thoroughly mixing an epoxy resin and a curing agent, and if necessary, a curing accelerator, an inorganic filler, a release agent, a silane coupling agent, and additives until they are uniform, using an extruder, kneader, roll, planetary mixer, or the like, as necessary. The form of the obtained resin composition can take various forms, such as a resin sheet, a prepreg, a liquid composition, and a solid powder, depending on the molding method.

[0053] When the curable resin composition of the present embodiment is in the form of a prepreg, for example, the curable resin composition of the present embodiment and / or a resin sheet are heated and melted to reduce the viscosity, and then impregnated into a fiber substrate to obtain the prepreg of the present embodiment. Furthermore, an organic solvent can be added as necessary to obtain a varnish-like composition (hereinafter, simply referred to as varnish). The curable resin composition of the present embodiment can be dissolved in a solvent such as toluene, xylene, acetone, methyl ethyl ketone, methyl isobutyl ketone, dimethylformamide, dimethylacetamide, or N-methylpyrrolidone as necessary to obtain a varnish, which can be impregnated into a substrate such as glass fiber, carbon fiber, polyester fiber, polyamide fiber, alumina fiber, or paper, and then heated and dried to produce a prepreg. The solvent used in this case is 10 to 70% by weight, preferably 15 to 70% by weight, of the mixture of the curable resin composition of the present embodiment and the solvent. The above prepreg is cut into a desired shape, laminated, and then the curable resin composition is heated and cured while applying pressure to the laminate by a press molding method, an autoclave molding method, a sheet winding molding method, or the like, to obtain the CFRP of the present embodiment. Furthermore, copper foil or an organic film can be laminated when laminating the prepreg.

[0054] Furthermore, the CFRP of this embodiment can be obtained by molding using a known method other than the above-mentioned method. For example, a resin transfer molding technique (RTM method) can be used, in which a carbon fiber substrate (usually a carbon fiber fabric) is cut, laminated, and shaped to produce a preform (a preform before being impregnated with resin), the preform is placed in a mold, the mold is closed, resin is injected to impregnate the preform, the resin is hardened, and the mold is opened to remove the molded product. Also usable are a type of RTM method, such as the VaRTM method, Seeman's Composite Resin Infusion Molding Process (SCRIMP) method, and the Controlled Atmospheric Pressure Resin Infusion (CAPRI) method, which is described in JP2005-527410A and which more appropriately controls the resin injection process, particularly the VaRTM method, by evacuating a resin supply tank to a pressure lower than atmospheric pressure, using circulatory compression, and controlling the net molding pressure.

[0055] In addition, other methods that can be used include the film stacking method, in which the fiber substrate is sandwiched between resin sheets (films), the method of attaching powdered resin to the reinforcing fiber substrate to improve impregnation, the molding method (Powder Impregnated Yarn) that uses a fluidized bed or fluid slurry method in the process of mixing the resin into the fiber substrate, and the method of blending resin fibers into the fiber substrate.

[0056] Examples of carbon fibers include acrylic, pitch, and rayon carbon fibers, and among them, acrylic carbon fibers having high tensile strength are preferably used. As the form of carbon fibers, twisted yarn, untwisted yarn, non-twisted yarn, etc. can be used, but untwisted yarn or non-twisted yarn is preferably used because it has a good balance between the formability and strength properties of the fiber-reinforced composite material.

[0057] The cured product obtained in this embodiment can be used for various applications other than the above-mentioned applications such as substrates and CFRP, etc. In particular, general applications in which thermosetting resins such as epoxy resins are used can be mentioned, such as adhesives, paints, coating agents, insulating materials (including electric wire coatings, etc.), semiconductor encapsulants, etc.

[0058] When the curable resin composition of this embodiment is applied to a semiconductor encapsulation material in particular, the curable resin composition of this embodiment is placed on a lead frame equipped with a semiconductor element, a semiconductor package substrate, and molded by a melt casting method, a transfer molding method, an injection molding method, a compression molding method, or the like, and further heated at 80 to 200° C. for 2 to 10 hours to obtain a cured product. Examples of semiconductor devices manufactured using this encapsulation material include potting, dipping, and transfer mold encapsulation for capacitors, transistors, diodes, light-emitting diodes, ICs, and LSIs, potting encapsulation for COB, COF, TAB, and the like of ICs and LSIs, underfill for flip chips, and encapsulation (including reinforcing underfill) when mounting IC packages such as QFP, BGA, and CSP.

[0059] When the curable resin composition of the present embodiment is applied to a substrate, it can be heated and melted to reduce the viscosity, and impregnated into reinforcing fibers such as glass fibers and polyamide fibers to obtain a prepreg. Specific examples thereof include glass fibers such as E glass cloth, D glass cloth, S glass cloth, Q glass cloth, spherical glass cloth, NE glass cloth, and T glass cloth, and / or organic fibers, but are not particularly limited thereto. The shape of the substrate is not particularly limited, but examples thereof include woven fabric, nonwoven fabric, roving, chopped strand mat, and the like. In addition, as the weaving method of the woven fabric, plain weave, saddle weave, twill weave, and the like are known, and these known weaves can be appropriately selected and used according to the intended use and performance. In addition, woven fabrics that have been subjected to fiber opening treatment or glass woven fabrics that have been surface-treated with a silane coupling agent or the like are preferably used. The thickness of the substrate is not particularly limited, but is preferably about 0.01 to 0.4 mm. Moreover, the varnish can be impregnated into reinforcing fibers and dried by heating to obtain a prepreg, which can be used to prepare a copper clad laminate (CCL). The obtained prepreg and CCL can be hot-press molded to prepare a laminate using the curable resin composition of the present embodiment. The laminate is not particularly limited as long as it has one or more prepregs, and may have any other layers. Moreover, a sheet-like adhesive can be obtained by applying the epoxy resin varnish onto a release film, removing the solvent under heating, and performing B-stage formation. This sheet-like adhesive can be used as an interlayer insulating layer in a multilayer board or an adhesive sheet when mounting a semiconductor. These curable resin compositions of the present embodiment can be suitably used for printed wiring boards, and can also be suitably used for special substrate materials such as package substrates and HDI (high density interconnect).

[0060] Examples of adhesives include adhesives for civil engineering, construction, automobiles, general office use, and medical use, as well as adhesives for electronic materials. Among these, adhesives for electronic materials include interlayer adhesives for multilayer boards such as build-up boards, die bonding agents, semiconductor adhesives such as underfills, underfills for reinforcing BGAs, and mounting adhesives such as anisotropic conductive films (ACFs) and anisotropic conductive pastes (ACPs), and are applicable to a variety of uses. EXAMPLES

[0061] The present invention will be described in more detail below with reference to synthesis examples and examples. The materials, processing contents, processing procedures, etc. shown below can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the specific examples shown below. Various analytical methods used in the examples are described below.

[0062] Various analytical methods were carried out under the following conditions. Epoxy equivalent The measurement is performed according to a method conforming to JIS K-7236, and the unit is g / eq. ·Softening point The measurement was performed according to JIS K-7234 and the unit is °C. ·ICI viscosity The measurement is performed according to a method conforming to JIS K-7117-2, and the unit is Pa·s.

[0063] ·GPC (gel permeation chromatography) analysis Manufacturer:Waters Column: Guard column SHODEX GPC KF-601, KF-602 KF-602.5, KF-603 Flow rate: 0.5ml / min. Column temperature: 40℃ Solvent used: THF (tetrahydrofuran) Detector: RI (Differential Refraction Detector) ·NMR analysis Equipment: AVANCE NEO 600MHz (Bruker) Measurement method: 13C(CDCl 3 ) Accumulation count: 10000 ·GC-MS analysis Instrument: 6890N inert MSD (Agilent) Column: HP-5MS 15m x 0.25mm x 0.25μm Carrier gas: He 1.0mL / min (constant flow mode) Oven: 50℃(2min)-10℃ / min-300℃(23min) Injection: 1μL, Split 30:1, 300℃ Ionization method: EI

[0064] [Example 1] A flask equipped with a stirrer, a reflux condenser, and a stirrer was charged with 137 parts by weight of YS Polystar K125 (m=3.3, n=4.4 in the above formula (2)), 300 parts by weight of epichlorohydrin (ECH, the same below), 65 parts by weight of dimethyl sulfoxide (DMSO, the same below), and 6 parts by weight of water, heated, stirred, and dissolved, and then 21 parts by weight of flake-shaped sodium hydroxide was charged in portions over 2 hours while maintaining the temperature at 45°C. Thereafter, the reaction was further carried out at 65°C for 2 hours and at 70°C for 30 minutes. Next, excess epichlorohydrin was distilled off under heating and reduced pressure, and 314 parts by weight of methyl isobutyl ketone was added to the residue and dissolved. This methyl isobutyl ketone solution was heated to 70°C, and 90 parts by weight of water, 8 parts by weight of methanol, and 8 parts by weight of 30% aqueous sodium hydroxide solution were added and reacted for 1 hour. After that, the reaction solution was repeatedly washed with water until the washings became neutral. Then, the methyl isobutyl ketone was distilled off from the oil layer under heating and reduced pressure to obtain 149 parts by weight of solid epoxy resin. The epoxy equivalent of the obtained epoxy resin was 340 g / eq., the softening point was 100°C, the ICI viscosity was 1.03 Pa s (150°C), and the weight average molecular weight was 830. The GPC results are shown in Figure 1.

[0065] [Comparative Example 1] An epoxy resin was synthesized as follows, with reference to the synthesis method described in Example 1 of Reference 1. 141 parts by weight of phenol and 1.4 parts by weight of boron trifluoride diethyl ether complex were charged into a flask equipped with a stirrer, a reflux condenser, and a stirring device, and 34 parts by weight of limonene were added dropwise at 80°C over 1 hour, followed by stirring for another 2 hours. Next, the mixture was washed three times with distilled water, and unreacted phenol was removed by distillation under reduced pressure with heating to obtain 62 parts by weight of a polyhydric phenol compound containing a cyclic terpene skeleton. Next, 60 parts by weight of the cyclic terpene skeleton-containing polyhydric phenol compound synthesized above, 171 parts by weight of epichlorohydrin, 74 parts by weight of DMSO, and 7 parts by weight of water were charged into a reaction vessel in a flask equipped with a stirrer, a reflux condenser, and a stirring device, and after heating, stirring, and dissolving, 24 parts by weight of flake-shaped sodium hydroxide was charged in portions over 2 hours while maintaining the temperature at 65°C. Then, the reaction was carried out by maintaining the temperature at 65°C for 30 minutes. After the reaction was completed, the by-product salt and DMSO were removed by washing with water. Next, excess epichlorohydrin was distilled off from this product under heating and reduced pressure. Next, methyl isobutyl ketone was added to the residue to dissolve it, 9 parts by weight of a 30% aqueous sodium hydroxide solution was added, and the reaction was carried out at 65°C for 1 hour, and the reaction solution was repeatedly washed with water until the washing solution became neutral. Next, 61 parts by weight of a liquid epoxy resin was obtained by distilling off methyl isobutyl ketone from the oil layer under heating and reduced pressure. The epoxy equivalent of the obtained epoxy resin was 242 g / eq., the ICI viscosity was 0.04 Pa·s (150°C), and the weight average molecular weight was 450. The GPC results are shown in Figure 2.

[0066] The physical properties were measured under the following conditions. <Heat resistance (Tg) measurement conditions> Dynamic viscoelasticity measuring instrument: TA-instruments, DMA-2980 Measurement temperature range: -30~280℃ Heating rate: 2℃ / min Tg: The peak point of Tan δ was taken as Tg. <Bending strength and elastic modulus measurement conditions> Equipment: Tensilon RTG-1310 (A&D) Sample size: Width 9mm x Length 64mm x Thickness 4mm Specification: Conforms to JIS K-6911 <IZOD Impact Test> Apparatus: IZOD impact tester DG-IB (Toyosha Seisakusho Co., Ltd.) Sample size: Disc with a diameter of 5 cm and a thickness of 4 mm Specification: Conforms to JIS K-6911

[0067] [Example 2, Comparative Example 2] Using the epoxy resins obtained in Example 1 and Comparative Example 1 as the main agent, phenol novolac resin (manufactured by Gunei Chemical Co., Ltd., softening point 83.6 °C) as the curing agent, and TPP (manufactured by Hokko Chemical Industry Co., Ltd.: triphenylphosphine) as the curing accelerator, they were mixed at the weight ratios shown in the formulation composition of 1, and cured under the curing conditions of 160 °C × 2 hours and 180 °C × 6 hours to prepare cured products.

[0068] [Example 3, Comparative Example 3] Using the epoxy resins obtained in Example 1 and Comparative Example 1 as the main agent, 4,4'-methylenebis(2,6-diethylaniline) (abbreviation; M-DEA, manufactured by Tokyo Chemical Industry Co., Ltd.) as the curing agent, they were mixed at the weight ratios shown in the formulation composition of Table 1, and cured under the curing conditions of 160 °C for 6 hours to prepare cured products.

[0069]

Table 1

[0070] From the results in Table 1, it was confirmed that the cured products of the examples of the present application are excellent in heat resistance and mechanical properties.

Claims

1. An epoxy resin obtained by reacting a phenol compound represented by the following formula (1) with epihalohydrin. 【Chemistry 1】 (In formula (1), C 1 and C. 2 Between 2 and C. 3 Between 3 and C. 4 Between 4 and C. 5 Between 5 and C. 6 Between and C 6 and C. 1 The dotted line between indicates that a single bond or a double bond may be present within the range permitted by the atomic valence. m and n are the average values ​​of the repeating numbers, and m is a real number satisfying 1<m≦5 and n is a real number satisfying 1<n≦10.)

2. 2. The epoxy resin according to claim 1, wherein the phenol compound represented by the formula (1) is obtained by adding a phenol to a cyclic terpene compound.

3. 2. The epoxy resin according to claim 1, having an epoxy equivalent of 280 g / eq. or more and 600 g / eq. or less.

4. A curable resin composition comprising the epoxy resin according to claim 1 and a curing agent.

5. A cured product obtained by curing the curable resin composition according to claim 4.

6. A carbon fiber reinforced composite material obtained by curing the curable resin composition according to claim 4.

7. The epoxy resin according to claim 1, wherein the phenol compound represented by the formula (1) is YS Polystar K125 (trade name, manufactured by Yasuhara Chemical Co., Ltd.).

Citation Information

Patent Citations

  • Epoxy compound and epoxy resin composition

    JP1992117420A